Problem of optimal strategy in the models of conflict redistribution of the resource space - Verigina, I. V.; Koshmanenko, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
The theory of conflict dynamical systems is applied to finding of the optimal strategy in the problem of redistribution of theresource space between two opponents. In the case of infinite fractal division of the space, we deduce an explicit formulafor finding the Lebesgue measure of the occupied territory in terms of probability distributions. In particular, this formulagives the optimal strategy for the occupation of the whole territory. The necessary and sufficient condition for the paritydistribution of the territory are presented.